Numerical and Experimental Test on an Innovative Device Based on Multiple Rotors in Line to Tap Clean Energy from Tidal and River Current - Coiro, D.P.; Scherillo, F.; G. Troise, G.; Bizzarrini, N.; Calise, G. (Journal of Technology Innovations in Renewable Energy, 2016)
The main object of this paper is to present the design and the results of an experimental test campaign on an innovative device for the exploitation of marine and river currents. The basic idea is to lay together one or more series of horizontal axis turbines in rows, each one connected to a generator placed on board a ship or a float. The whole system is sustained by a series of buoys, in this way is possible to avoid expensive submarine installations. All the work has been carried out at the Department of Industrial Engineering of the University of Naples "Federico II" and the test campaign has been first performed in the naval towing tank belonging to the same Department and then in real conditions in Messina Strait between Sicily island and mainland. This location is the only one in Italy suitable as test site thanks to a highly regular tidal current reaching a maximum speed of 3 m/s. The turbine's blade was first carefully designed with particular care for the cavitation problems. Two different series of experimental tests on a reduced scale model in the naval tank aimed to optimize the general layout of the device and the tests performed in Messina Strait mainly aimed to confirm the feasibility of the system and to evaluate its response in real operating conditions. The tests have confirmed the good dynamic behavior of the whole system and its feasibility to be scaled up to real scale.